Mapa de percepção: a formação da imagem dos programas de mestrado em administração na cidade do Rio de Janeiro - Ghosn, Gibran Habib Abi (2018)
The understanding of individual’s perception position perceived of mba programs is essential to know consumer’s behavior, to adopt marketing strategies, to deal with the competition, and others. Ten perceptual maps are proposed in this dissertation, in a practical and simplified way, using dimensions found by statistical methodology, in order to investigate how mba’s services are positioned, considering personal’s perceptions. The data were collected through a face-to-face questionnaire and analyzed using factor analysis technique. The achieved results show that each masters business program has its own peculiarities, its strengths and weaknesses. Finally, we must bear in mind that reality can be different from the perception observed in the data.